2018
DOI: 10.1371/journal.pone.0209480
|View full text |Cite
|
Sign up to set email alerts
|

Live human assessment of depth-dependent corneal displacements with swept-source optical coherence elastography

Abstract: PurposeTo assess depth-dependent corneal displacements in live normal subjects using optical coherence elastography (OCE).MethodsA corneal elastography method based on swept-source optical coherence tomography (OCT) was implemented in a clinical prototype. Low amplitude corneal deformation was produced during OCT imaging with a linear actuator-driven lens coupled to force transducers. A cross-correlation algorithm was applied to track frame-by-frame speckle displacement across horizontal meridian scans. Intra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 42 publications
(55 reference statements)
1
42
0
1
Order By: Relevance
“…OCE with an external excitation source has been used to assess the mechanical properties of the cornea in vivo using dynamic wave propagation methods as well as quasistatic techniques. 19,21,42 However, these techniques have a variety of limitations in acquisition and analysis, such as patient discomfort, nonlinear mechanical behavior, or lengthy imaging times. Since the technique presented in this work does not require complex wave analysis or additional tools to determine tissue mechanical properties, we can assess the mechanical properties of the cornea using only a phase-sensitive OCT system, a ubiquitous tool in ophthalmology and optometry clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCE with an external excitation source has been used to assess the mechanical properties of the cornea in vivo using dynamic wave propagation methods as well as quasistatic techniques. 19,21,42 However, these techniques have a variety of limitations in acquisition and analysis, such as patient discomfort, nonlinear mechanical behavior, or lengthy imaging times. Since the technique presented in this work does not require complex wave analysis or additional tools to determine tissue mechanical properties, we can assess the mechanical properties of the cornea using only a phase-sensitive OCT system, a ubiquitous tool in ophthalmology and optometry clinics.…”
Section: Discussionmentioning
confidence: 99%
“…8,[15][16][17][18] Typically, these techniques measure the corneal response to different external forces. [19][20][21][22][23] However, there is growing interest in assessing the tissue mechanical response to intrinsic physiological forces. 24 For example, hemodynamics within the eyeball can cause ocular tissue to experience pulsatile motion known as the ocular pulse.…”
Section: Introductionmentioning
confidence: 99%
“…While dynamic measurements allow fast imaging speeds and hence reduce motion artifacts, longer time scales, which are relevant for corneal reshaping and disease progression, are not accessible. The only quasi-static assessment of in vivo corneal biomechanics combines OCE with central applanation of the cornea by a gonioscopy lens (De Stefano et al, 2018) requiring contact. Here, spatially resolved cross-sectional maps of axial corneal displacements were obtained by tracking speckle deformation during the applanation (De Stefano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A lambda (λ) trigger using a fiber Bragg grating (FBG) as well as a kclock generated by a Mach-Zehnder interferometer (MZI) have been introduced to improve the phase stability, making SS-OCT a more attractive setup in OCE applications 28 . In recent years, several OCE systems based on conventional SS-OCT (SS-OCE COV ) have been proposed 14,[29][30][31][32][33][34][35] , and their feasibilities have been validated through ex vivo and in vivo experiments, demonstrating great potential towards clinical translation. Although these studies have reported subnanometre displacement sensitivities, this is achieved only in system charaterization where a simple common-path configuration is used.…”
Section: Introductionmentioning
confidence: 99%